Caridina longiacuta, a new species of freshwater atyid shrimp (Decapoda, Atyidae) from Hunan Province, China - Guo, Zhao-Liang; Wang, Xiao-Qing (Zootaxa, 2005)
A new atyid species, Caridina longiacuta, is described and illustrated from Hunan Province, China. Caridina longiacuta is characterized by its long rostrum, long finger-like process on the anterolateral angle of basal antennular segment, the narrow scaphocerite, the segmental ratios of third maxilliped, the shape and spination of its posterior telsonic margin, and small eggs. Also, Caridina cantonensis Yu, 1938 is reported from Hunan Province for the first time.